Impact of the Residual SYNTAX Score on Outcomes of Revascularization in Patients with ST-Segment Elevation Myocardial Infarction and Multivessel Disease - Mohamed Loutfi (Clinical Medicine Insights: Cardiology, 2016)
Primary percutaneous coronary intervention (P-PCI) has become the preferred reperfusion strategy in ST-elevation myocardial infarction (STEMI) when performed by an experienced team in a timely manner. However, no consensus exists regarding the management of multivessel coronary disease detected at the time of P-PCI. Aim The aim of this study was to evaluate the use of the residual SYNTAX score (rSS) following a complete vs. culprit-only revascularization strategy in patients with STEMI and multivessel disease (MVD) to quantify the extent and complexity of residual coronary stenoses and their impact on adverse ischemic outcomes. Methods Between October 1, 2012, and November 30, 2013, we enrolled 120 consecutive STEMI patients with angiographic patterns of multivessel coronary artery disease (CAD) who had a clinical indication to undergo PCI. The patients were subdivided into those who underwent culprit-only PCI (60 patients) and those who underwent staged-multivessel PCI during the index admission or who were staged within 30 days of the index admission (60 patients). Both the groups were well matched with regard to clinical statuses and lesion characteristics. Clinical outcomes at one year were collected, and the baseline SYNTAX score and rSS were calculated. Results The mean total stent length (31.07 ± 12.7 mm vs. 76.3 ± 14.1 mm) and the number of stents implanted per patient (1.34 ± 0.6 vs. 2.47 ± 0.72) were higher in the staged-PCI group. The rSS was higher in the culprit-only PCI group (9.7 ± 5.7 vs. 1.3 ± 1.99). The angiographic and clinical results after a mean follow-up of 343 ± 75 days demonstrated no significant difference in the occurrence of in-hospital Major Adverse Cardiac and Cerebrovascular Events (MACCE) between both the groups (6.7% vs. 5%, P = 1.000). However, patients treated with staged PCI with an rSS ≤8 had significant reductions in one-year MACCE (10.7% vs. 30.5%, P = 0.020*), death/Myocardial infarction (MI)/Cerebrovascular accident (CVA) (5% vs. 13.8%, P = 0.016*), and repeat revascularization (4.8% vs. 25%, P = 0.001*). We found that culprit-only, higher GRACE risk scores at discharge and an rSS >8 were independent predictors of MACCE at one year. Conclusions Staged PCI that achieves reasonable complete revascularization (rSS ≤8) improves mid-term survival and reduces the incidence of repeat PCI in patients with STEMI and MVD. Nonetheless, large-scale randomized trials are required to establish the optimal revascularization strategy for these high-risk patients.